2019
DOI: 10.1098/rspb.2019.0260
|View full text |Cite
|
Sign up to set email alerts
|

Community disassembly and disease: realistic—but not randomized—biodiversity losses enhance parasite transmission

Abstract: Debates over the relationship between biodiversity and disease dynamics underscore the need for a more mechanistic understanding of how changes in host community composition influence parasite transmission. Focusing on interactions between larval amphibians and trematode parasites, we experimentally contrasted the effects of host richness and species composition to identify the individual and joint contributions of both parameters on the infection levels of three trematode species. By combining experimental ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 46 publications
5
48
0
Order By: Relevance
“…This result supports two recent studies that found that the relationship between host and parasite richness was contingent on characteristics of host and parasite communities (Johnson et al, 2016;Wood et al, 2018). Furthermore, host community assembly is linked to parasite transmission Johnson et al, 2019;Johnson, de Roode, & Fenton, 2015;Joseph, Mihaljevic, Orlofske, & Paull, 2013), and our results suggest that contingencies in the relationship between host and parasite richness during host community assembly can emerge as a consequence of changing parasite transmission.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result supports two recent studies that found that the relationship between host and parasite richness was contingent on characteristics of host and parasite communities (Johnson et al, 2016;Wood et al, 2018). Furthermore, host community assembly is linked to parasite transmission Johnson et al, 2019;Johnson, de Roode, & Fenton, 2015;Joseph, Mihaljevic, Orlofske, & Paull, 2013), and our results suggest that contingencies in the relationship between host and parasite richness during host community assembly can emerge as a consequence of changing parasite transmission.…”
Section: Discussionsupporting
confidence: 91%
“…Our manipulation of initial host diversity was intended to represent different scenarios of biodiversity loss. But not all biodiversity loss is the same, and the process of community disassembly during biodiversity loss can influence parasite transmission (Johnson et al, 2019;Joseph et al, 2013;Ostfeld & LoGiudice, 2003), potentially confounding responses to initial richness and parasite transmission during community assembly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diversity and dynamics of a community of host species can have a significant influence on pathogen dynamics and vice versa (Becker et al 2014;Han et al 2015;Bienentreu 2019;Johnson et al 2019). Pathogen transmission and infection prevalence are influenced by diversity, density, and abundance of suitable host species (and life stages) in the affected system (Miller et al 2011;Venesky et al 2014;Brunner et al 2015;Muths et al 2020).…”
Section: Host Community and Densitymentioning
confidence: 99%